Awareness campaigns of atrial fibrillation as an opportunity for early detection by pharmacists: an international cross-sectional study - da Costa, Filipa Alves; Mala-Ladova, Katerina; Lee, Vivian; Tous, Salvador; Papastergiou, John; Griffiths, Dale; Chaumais, Marie-Camille; Hersberger, Kurt E; Viola, Reka; Paulino, Ema; Lobban, Trudie; Neubeck, Lis; et al. (Journal of thrombosis and thrombolysis, 2020)
Atrial fibrillation (AF) accounts for up to one third of strokes, one of the lead mortality causes worldwide. The European Society of Cardiology guidelines recommend opportunistic screening as a means to increase the odds of early detection and institution of appropriate treatment according to risk factors identified. However, in most countries there are various barriers to effective uptake of screening, including low awareness. The Atrial Fibrillation Association is a patient association engaged with raising awareness of AF. Establishing a partnership with the International Pharmacists for Anticoagulation Care Taskforce, we set as goals to test a model for raising awareness of AF involving pharmacists globally; and to identify barriers and enablers to its implementation. A cross-sectional study was conducted during the Arrhythmia Alliance World Heart Rhythm Week. Pharmacists from 10 countries invited individuals (≥ 40 years; without anticoagulation therapy of AF) to participate in the awareness campaign. Participants agreeing were engaged in the early detection of AF (EDAF) using pulse palpation. Individuals with rhythm discrepancies were referred and prospectively assessed to have information on the proportion of confirmed diagnosis, leading to estimate the detection rate. Interviews with country coordinators explored barriers and enablers to implementation. The study involved 4193 participants in the awareness campaign and 2762 in the EDAF event (mean age 65.3 ± 13.0), of whom 46.2% individuals were asymptomatic, recruited across 120 sites. Most common CHA2DS2-VASc risk factor was hypertension. Among 161 patients referred to physician, feedback was obtained for 32 cases, of whom 12 new arrhythmia diagnoses were confirmed (5 for AF, 2 for atrial flutter), all among elders (≥ 65 years). Qualitative evaluation suggested a local champion to enable pharmacists' success; technology enhanced engagement amongst patients and increased pharmacists' confidence in referring to physicians; interprofessional relationship was crucial in success. This study suggests pharmacists can contribute to greater outreach of awareness campaigns. Effective communication pathways for inter-professional collaboration were suggested enablers to gain full benefits of EDAF.
Keywords: dospělí; Female; Health Education; Atrial Fibrillation; Adult; ženské pohlaví; průřezové studie; Internationality; lidé; internacionalita; Pharmacists; Aged, 80 and over; časná diagnóza; Humans; Cross-Sectional Studies; Male; Aged; Health Knowledge, Attitudes, Practice; zdraví - znalosti, postoje, praxe; farmaceuti; Early Diagnosis; fibrilace síní; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; zdravotní výchova